Comparison of compliance among patients with pediatric amblyopia undergoing virtual reality-based and traditional patching method training - Li, Li; Xue, Hailan; Lai, Taichen; Xue, Ying; Luo, Gang (Frontiers in Public Health, 2022)
Introduction This study aimed to compare compliance between pediatric patients with amblyopia undergoing a smartphone virtual reality-based training method (EYEBIT) and those receiving traditional patching method training. Methods A crossover design was adopted in this study. The enrolled children (n = 76) were randomized into the traditional patching and EYEBIT training method groups. The patients received training methods once a day for 2 h and 1 h in the patching and EYEBIT groups, respectively. Follow-up assessments involved interviews with parents regarding children's compliance and questionnaire-based interviews with children; compliance rating was compared between the methods. Results All children completed the training and follow-up assessments. There were significant differences in parent and children compliance-related behavior and attitudes between the two training methods (p < 0.05). The EYEBIT method was associated with better compliance than the traditional patching method. Significant correlations were observed among compliance components in both methods. In the correlation analysis between the two groups, the research results showed that in the EYEBIT group, the correlation between children's compliance behaviors and children's compliance attitudes, the correlation between children's compliance behaviors and parents' compliance behaviors, and the correlations between children's compliance attitudes and parents' compliance attitudes were all negatively correlated, and in the traditional patching group, the above three correlation analysis results were all positive. Conclusion The use of the EYEBIT method may improve compliance in children with amblyopia; this method appears acceptable to the parents of children with amblyopia.